Antibacterial, antifungal, and antibiofilm activities of biogenic zinc nanoparticles against pathogenic microorganisms - Lopez Venditti, Eliana Daniela; Crespo Andrada, Karina Fernanda; Bustos, Pamela Soledad; Maldonado Torales, Manuela; Manrrique Hughes, Iván; Paraje, María Gabriela; Guiñazú, Natalia (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe increasing resistance to antimicrobial drugs has prompted global efforts to combat pathogenic bacteria and fungi. The World Health Organization’s recent report underscores the urgent need for innovative antimicrobial strategies to address infections caused by Staphylococcus aureus, Escherichia coli, Candida albicans, and Candida tropicalis. This study presents a comparative evaluation of the effects of biogenically synthesized zinc nanoparticles (ZnNPs) from Pseudomonas aeruginosa, highlighting their effectiveness against both planktonic and sessile forms of these tested pathogens.MethodsThe antimicrobial effects were assessed using the Kirby-Bauer disk diffusion method, broth microdilution, and time-kill assays. Biofilm formation and eradication were evaluated through crystal violet staining, resazurin assays, and colony-forming unit quantification. Additionally, the oxidative and nitrosative stress toxicity mechanisms triggered by ZnNPs, particularly those related to cellular stress, were investigated.ResultsThe results demonstrated that ZnNPs exhibit concentration-dependent inhibitory effects on both prokaryotic and eukaryotic microorganisms. ZnNPs inhibit biofilm formation by up to 50% in E. coli and yeast species, and up to 80% in S. aureus.DiscussionThese antibiofilm activities were attributed to disruptions in cellular stress metabolism, primarily driven by nitrosative stress through enhanced production of reactive nitrogen intermediates. ZnNPs synthesized through green methods offer significant advantages due to their biocompatibility and potential biomedical applications. These findings advance our understanding of ZnNPs in combating biofilm-associated infections, offering promising strategies to address pathogenic bacteria and fungi, which pose a critical threat to global health.